SN 2018zd: an unusual stellar explosion as part of the diverse Type II Supernova landscape - Zhang, Jujia; Wang, Xiaofeng; József, Vinkó; Zhai, Qian; Zhang, Tianmeng; Filippenko, Alexei V; Brink, Thomas G; Zheng, WeiKang; Wyrzykowski, Łukasz; Mikołajczyk, Przemysław; Huang, Fang; Rui, Liming; et al. (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT We present extensive observations of SN 2018zd covering the first ∼450 d after the explosion. This SN shows a possible shock-breakout signal ∼3.6 h after the explosion in the unfiltered light curve, and prominent flash-ionization spectral features within the first week. The unusual photospheric temperature rise (rapidly from ∼12 000 to above 18 000 K) within the earliest few days suggests that the ejecta were continuously heated. Both the significant temperature rise and the flash spectral features can be explained by the interaction of the SN ejecta with the massive stellar wind ($0.18^{+0.05}_{-0.10}\, \rm M_{\odot }$), which accounts for the luminous peak ($L_{\rm max} = [1.36\pm 0.63] \times 10^{43}\, \rm erg\, s^{-1}$) of SN 2018zd. The luminous peak and low expansion velocity (v ≈ 3300 km s−1) make SN 2018zd like a member of the LLEV (luminous SNe II with low expansion velocities) events originating due to circumstellar interaction. The relatively fast post-peak decline allows a classification of SN 2018zd as a transition event morphologically linking SNe IIP and SNe IIL. In the radioactive-decay phase, SN 2018zd experienced a significant flux drop and behaved more like a low-luminosity SN IIP both spectroscopically and photometrically. This contrast indicates that circumstellar interaction plays a vital role in modifying the observed light curves of SNe II. Comparing nebular-phase spectra with model predictions suggests that SN 2018zd arose from a star of $\sim 12\, \rm M_{\odot }$. Given the relatively small amount of 56Ni ($0.013\!-\!0.035 \rm M_{\odot }$), the massive stellar wind, and the faint X-ray radiation, the progenitor of SN 2018zd could be a massive asymptotic giant branch star that collapsed owing to electron capture.